Health outcomes in those who have been victims of knife crime: a protocol for a systematic review and meta-analysis - Joht Singh Chandan; Siddhartha Bandyopadhyay; James Martin; Illin Gani; Anna Pathmanathan (BMJ Open)
Introduction Knife-enabled crime is a UK public health issue leading to substantial impacts on society, victims and their families, as well as additional strain on the healthcare system. Despite the increase in knife-enabled crime and the overwhelming consequences, there is a lack of comprehensive studies exploring the long-term health outcomes of knife crime victims in the UK. The research gap hinders the development of more targeted secondary preventative interventions, resource allocation and public awareness campaigns. This systematic review aims to identify the long-term health outcomes of knife crime victims, therefore providing valuable knowledge for stakeholders, health practitioners and policymakers for a more effective public health response.Methods and analysis A comprehensive search strategy was developed, focusing on four key concepts: study design, knife-related offences, outcomes and risk. Databases being searched include MEDLINE, EMBASE, PsycINFO, ProQuest Criminology Collection, Web of Science Core Collection, Google Scholar and OpenGrey. Reference lists and forward citations will be inspected for further suitable literature. The study selection will involve two independent reviewers screening the studies from the search, with disagreements resolved by a third reviewer. All UK quantitative research on long-term health outcomes of knife crime victims will be included in the review. Covidence will be used to efficiently manage data. A data extraction form has been developed which will summarise key aspects of each study that will be included in the review. Methodological Index for Non-Randomised Studies quality assessment checklist will be used to assess the studies and the Newcastle-Ottawa Scale will assess the risk of bias in each study. Findings will be narratively synthesised, and if heterogeneity is sufficient, a meta-analysis will be conducted.Ethics and dissemination Ethics approval is not required for this study as no original data will be collected. The results will be disseminated through a peer-reviewed publication and conference presentation.